Proceedings of the 26th Australian Computer-Human Interaction Conference on Designing Futures: The Future of Design 2014
DOI: 10.1145/2686612.2686629
|View full text |Cite
|
Sign up to set email alerts
|

Smartcasting

Abstract: We introduce and formally evaluate smartcasting: a smartphone-based Ray Casting implementation for 3D environments presented on large, public, autostereoscopic displays. By utilizing a smartphone as an input device, smartcasting enables "walk up and use" interaction with large displays, without the need for expensive tracking systems or specialized pointing devices. Through an empirical validation we show that the performance and precision of smartcasting is comparable to a Wiimotebased raycasting implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…One of the first works adopting this approach focused on the use of multiple devices to improve the interaction with whiteboards [49]. A large part of the works related to this area aims to improve and facilitate interaction with large displays: content sharing [15,42,35], pointing [29], 3D manipulations [47,45,46]. In the XR field, researchers identified quite early the potential of combining mobile devices with HMDs: Feiner et al [21] in 1997 used a tablet to display a second-level menu as well as detailed information about augmented data in the HMD to compensate for its low resolution.…”
Section: Combining Mobile Devices and Hmdsmentioning
confidence: 99%
“…One of the first works adopting this approach focused on the use of multiple devices to improve the interaction with whiteboards [49]. A large part of the works related to this area aims to improve and facilitate interaction with large displays: content sharing [15,42,35], pointing [29], 3D manipulations [47,45,46]. In the XR field, researchers identified quite early the potential of combining mobile devices with HMDs: Feiner et al [21] in 1997 used a tablet to display a second-level menu as well as detailed information about augmented data in the HMD to compensate for its low resolution.…”
Section: Combining Mobile Devices and Hmdsmentioning
confidence: 99%
“…Early work in this domain leveraged the touchscreen for input, essentially using the device as a drawing pad [23], a mouse plus sketch surface [39], or a touchpad [2,16]. More recently, the ubiquity of accelerometers and gyroscopes in these devices has made it possible to mimic freehand pointing techniques [18,26,33].…”
Section: Distant Pointing Techniquesmentioning
confidence: 99%
“…Recent research has shown that freehand pointing with a phone performs on par with the Nintendo Wiimote [26], and that freehand pointing with a smartwatch performs at near parity with Vicon-based freehand distal pointing [18]. As researchers, we believe that distal pointing with ubiquitous personal devices holds the most near-term promise for everyday public display interaction: Essentially, rather than augmenting the entire world or requiring potential users to identify and obtain relevant objects, if the input device is either a smartphone or a smartwatch, the vast majority of people already own and have with them their interaction platform.…”
Section: Distant Pointing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Free-space gestural input is an active area of research for ubiquitous display interaction (e.g., [1,19,20]) These techniques enable users to quickly and seamlessly interact with nearby displays, and have many practical advantages. To name only a few: proprioperceptive interaction allows one to avoid focusing on the physical input device; hand and arm gestures can naturally combine intended target and command into a seamless whole; given gestures' role in interpersonal communication, there is some consensus on gesture meaning.…”
Section: Introductionmentioning
confidence: 99%